Therapeutic spaces of care farming: Transformative or ameliorating?. (April 2019) - Kaley, Alexandra; Hatton, Chris; Milligan, Christine
Abstract: Since Wil Gesler's earliest articulation (Gesler, 1992; Gesler, 1996) key thinkers in the field of therapeutic landscapes have sought to emphasise the embodied, contextual and wholly relational nature of the relationship that exists between people and place. However, the extant research has tended to focus on the relational healing experience as this occurs 'in the moment' and with reference to a specific location or site of healing, with less attention being paid to what happens to people when they return to their ordinary or everyday places. In this paper, we reflect on findings from visual ethnographic work (including photography and film) that explored the therapeutic landscape experiences of people with intellectual disabilities engaged in care farming interventions for health and wellbeing. The study also recruited farm staff and family members or carers to take part, and comprised 20 participants in total. Having identified a gap in our understanding, consideration is given to wider impact that engaging in these sorts of activities had on the everyday lives of the participants in this study. We argue that this study has identified two types of therapeutic journey that broadly fit the experiences of study participants. The first type of journey denotes landscape experiences that are transformative. Here the therapeutic power of the care farm landscape resides in the ability of activities conducted on care farms to influence other aspects of participants' lives in ways that promote wellbeing. By contrast, there is another type of journey where the therapeutic power of the care farm resides in its ability to ameliorate challenging or harmful life situations, thus offering people a temporary site of respite or refuge. We conclude that these findings denote an important development for this sub-field of health geography, not only because they draw attention to the transformative power of the therapeutic encounter, but also the broader socio-spatial environments in which people live and ways in which these can limit that power. Highlights: A visual ethnographic study on the role of care farms as therapeutic spaces. Focuses on the experiences of people with intellectual disabilities. Utilises the concept of therapeutic landscapes as a theoretical framework. Draws critical attention to the transformative power of the therapeutic encounter.